BRUCELLAR UVEITIS IN EASTERN INDIA - Sen, Anindita; Banerjee, Parthajit; Dutta, Devarati; Pal, Manas; Ray, Atanu; Das, Satadal (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Brucellosis- one of the major zoonotic diseases, still remains an uncontrolled problem, in regions of high endemicity. Ophthalmic brucellosis is not studied and overlooked in most developing countries. Considering the severe outcome of undiagnosed ophthalmic brucellosis, in this paper we made attempts to find out whether this disease still remains a health problem in a South East Asian developing country, where study of this disease is largely neglected. Methods This study was carried out over a one year period from January 2015 to December 2015. Blood samples were collected from clinically confirmed cases of uveitis and they were subjected to five serological and one genus specific molecular investigations, for the detection of Brucella infection. Results Out of 20 uveitis cases, 4 (20%) cases confirmed as brucellar uveitis, by serological tests followed by PCR confirmation. After treatment of brucellosis all the four patients were recovered uneventfully. Conclusion: Brucella infection involving the eye is still a significant problem in South East Asian countries; hence in all uveitis cases in this reason brucellosis should be excluded by available laboratory tests.Government of India (Dept. of Biotechnology the major zoonotic diseases, still remains an uncontrolled problem, in regions of high endemicity. Ophthalmic brucellosis is not studied and overlooked in most developing countries. Considering the severe outcome of undiagnosed ophthalmic brucellosis, in this paper we made attempts to find out whether this disease still remains a health problem in a South East Asian developing country, where study of this disease is largely neglected. Methods This study was carried out over a one year period from January 2015 to December 2015. Blood samples were collected from clinically confirmed cases of uveitis and they were subjected to five serological and one genus specific molecular investigations, for the detection of Brucella infection. Results Out of 20 uveitis cases, 4 (20%) cases confirmed as brucellar uveitis, by serological tests followed by PCR confirmation. After treatment of brucellosis all the four patients were recovered uneventfully. Conclusion: Brucella infection involving the eye is still a significant problem in South East Asian countries; hence in all uveitis cases in this reason brucellosis should be excluded by available laboratory tests.